ANALISA KUAT TEKAN BETON MENGGUNAKAN PASIR APUNG - Abdul Gaus; Imran Imran; Liska Novianti (Journal of Science and Engineering, 2018)
Pumice sand is a bright colored butian type, containing foam made from glass-walled bubbles andusually referred to as silicate volcanic glass granules. This pumice sand can be used as a substitutefor normal sand as fine aggregate in a mixture of concrete mix. Based on the characteristic testexamination, it can be seen that in testing the characteristics of pumice sand to the specificationsof normal sand in specific gravity testing and weight testing of quicksand obtained results thatare smaller than the specifications of normal sand and absorption tests obtained results greaterthan specifications on normal sand. The results of the normal sand compressive strength at BN is250.95 kg /cm2 while the results of the floating sand concrete compressive strength on BPA is224, 965 kg /cm2. Based on the research it can be concluded that with the same quality of concrete,the quality of K-250 is different in comparison to the compressive strength of concrete in normalsand and pumice sand concrete shows almost the same results. Therefore, more in-depth researchis needed regarding the use of pumice sand instead of normal sand in a mixture of concrete mix.